Covalent assembly of nanoparticles as a peptidase-degradable platform for molecular MRI - Francisco Perez-Balderas (Nature Portfolio, 2017)
Iron oxide microparticles (MPIO) are better MRI contrast agents than nanoparticles, but are of limited clinical use as they are not degradable and so risk toxicity. Here the authors present an iron oxide microparticle MRI contrast agent with peptide linkers that enable degradation into non-toxic nanoparticlesin vivo.